Color Masking of Two Types of Medium Translucency Lithium Disilicate Ceramic Restorations by Spectrophotometry - T Rostamzadeh; S Alipour; F Golsorkhtabar (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: One of the problems in aesthetic treatment is the fabrication of monolithic ceramic restorations that have both the ability to cover discolored substrate and appropriate translucency so that it can have similar appearance to the remaining dental structure. The aim of this study was to determine the color coverage of two types of medium translucency lithium disilicate (LDS) ceramic restorations by spectrophotometry. Methods: In this in-vitro study, 15 A2 colored LDS discs using heat-pressed technique were prepared in two methods: MT monolithic LDS discs (thickness of 1.5 mm) and core-veneer discs (0.9 mm MT veneer and 0.6 mm high opacity core). The discs were placed on 3 substrates: amalgam, composite and non-precious gold-colored alloy (NPG). Therefore, there were five groups (n=3); monolithic discs on amalgam (ML-A), monolithic discs on NPG (ML-NPG), monolithic discs on composite (ML-C), core-veneer discs on amalgam (H-A) and core-veneer discs on NPG (H-NPG). The color coordinates of samples were measured three times under the same lighting conditions on black and white backgrounds. CIEDE 2000 (ΔE00) and translucency parameter (TP) were calculated. One-way analysis of variance and Post-hoc Tuckey test at significance level of 0.05 were used for analysis. Findings: The highest and the lowest value of ΔE00 was observed in H-NPG (6.80±0.73) and H-A (1.43±0.19) groups, respectively. There was a significant difference between the studied groups in terms of ΔE00 (p<0.001). The highest and the lowest amount of TP was observed in H-NPG (8.33±0.14) and ML-NPG (2.53±0.82) groups, respectively. There was a significant difference between the studied groups in terms of translucency parameters (p<0.001). Conclusion: Monolithic LDS disc covers NPG substrate better and LDS core-veneer disc covers amalgam substrate better.